Output tracking control of delayed switched systems via state-dependent switching and dynamic output feedback. (May 2019) - Yang, Dan; Li, Xiaodi; Qiu, Jianlong
Abstract: This paper investigates the problem of output tracking control for a class of delayed switched linear systems via state-dependent switching and dynamic output feedback control. A state-dependent switching rule and the switching regions are proposed. Then the stability and tracking performance analysis are proposed based on single Lyapunov function technique, respectively. The design problem of dynamic output feedback controllers can be solved efficiently by using linear matrix inequalities (LMIs) toolbox. Finally, a simulation example is given to illustrate the effectiveness of the proposed method.